A molecular phylogenetic evaluation of the Ramalina siliquosa complex, with notes on species circumscription and relationships within Ramalina. (May 2020) - LaGreca, Scott; Lumbsch, H. Thorsten; Kukwa, Martin; Wei, Xinli; Han, Jeong Eun; Moon, Kwang Hee; Kashiwadani, Hiroyuki; Aptroot, André; Leavitt, Steven D.
Abstract: Lichens of the Ramalina siliquosa complex dominate seashore cliffs in Europe and South-East Asia, but their taxonomy has been vigorously debated for over a century. On many cliffs, they exhibit a bewildering zonation of chemotypes that resembles the classic zonation of organisms that occupy the littoral zone below. Do the chemotypes represent separate species, or infraspecific variation? To better understand the systematics of this group, sequences from four genetic loci (ITS, IGS, RPB1 and RPB2 ) were obtained for 59 samples from Denmark, France, Iceland, Norway, UK, Japan and Korea, including all major chemotypes. Maximum likelihood analysis of these sequences, together with sequences from 36 other Ramalina species, reveals that the complex comprises two distinct phylogenetic lineages, each including multiple chemotypes. These two putative species-level lineages correspond to the currently accepted taxa R. cuspidata and R. siliquosa . There is no evidence that these two taxa are phylogenetic sister species. Consequently, the explanation of this chemotype complex as an example of 'sibling speciation' is rejected. Specimens traditionally called ' R . siliquosa ' from South-East Asia form a third clade, identified here as R . semicuspidata, with an additional, divaricatic acid chemotype. Other results include a robustly supported clade of Ramalina species that produce medullary depsides and depsidones; this clade includes another well-supported clade of south-eastern United States coastal plain and tropical Ramalina species. By contrast, large, strap-shaped Ramalina species that lack medullary depsides and depsidones occur in separate lineages. In addition, close relationships between the following groups of species are indicated: R. farinacea with R. subfarinacea ; R . fraxinea with R. leptocarpha, R. menziesii and R. subleptocarpha ; R. sinensis with R. unifolia . Furthermore, a new, variolaric acid-only chemotype is reported for R . farinacea, and a new, acid-deficient chemotype is reported for a more broadly circumscribed R. culbersoniorum .